Contributory Negligence in the Twenty-First Century: An Empirical Study of Trial Court Decisions - Goudkamp, J; Nolan, D (Wiley, 2016)
In this paper we report the results of an empirical study of the practical operation of the contributory negligence doctrine in the courts of England and Wales since the turn of the Twenty-First Century. For the purposes of the study, we analysed 273 trial court decisions. The two central questions that we looked at were (1) how often a defendant’s plea of contributory negligence was successful; and (2) by how much a claimant’s damages were reduced when a finding of contributory negligence was made. We also considered the extent to which the answers to these questions depended on the following variables: (1) the claimant’s age; (2) the claimant’s gender; (3) the type of damage suffered by the claimant; (4) the contextual setting of the claim; and (5) the year of the decision. Our study uncovered a number of important truths about the contemporary operation of the contributory negligence doctrine hidden in this mass of case law. Our findings will be of considerable interest to both scholars and practitioners of private law.